Management of Cocoa Bean Processing Business PT Perkebunan Nusantara XII Kendenglembu Plantation - Roudlotul Badi'ah; Yoga Dwi Anugrahadi; Evi Maya Odelia; Ika Korika Swasti (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study aims to determine the human resource, operational, and marketing management of cocoa beans at PTPN XII Kendenglembu Gardens. This study uses qualitative research methods with data collection techniques through observation, interviews, documentation, and literature. Data analysis using the Interactive Model starts with data collection, condensation, data presentation, and drawing conclusions or data verification. The results showed that human resource management at PT PTPN XII Kebun Kendenglembu, namely the status and remuneration system for casual and wholesale field workers; worker welfare includes training, education, hajj financing, health, giving, and other programs; development of certain levels at PTPN XII through management trainee programs, talent management, and career planning. Operational management of cocoa bean processing at PTPN XII Kendenglembu Plantation starts from receiving and weighing cocoa beans, fermentation; drying cocoa beans; drying cocoa beans; tempering and sorting cocoa beans; ready warehouse. While the marketing management at PTPN XII Kendenglembu Gardens, the cocoa bean products produced are dry cocoa beans, Cocoa Edel and Cocoa Bulk. The price of Edel Cocoa beans is considered the most expensive when compared to Bulk Cocoa. Edel Cocoa marketing is prioritized for export market share, and Bulk Cocoa is primarily local. Promotion is done directly and indirectly.